Hypoxia and angiogenesis in rheumatoid arthritis. - Taylor, P; Sivakumar, B (2005)
PURPOSE OF REVIEW: Angiogenesis is a prominent feature of rheumatoid synovitis. Although new blood vessels deliver oxygen to the augmented inflammatory cell mass, the neovascular network is dysfunctional and fails to restore tissue oxygen homeostasis, so that the rheumatoid joint remains a markedly hypoxic environment. The purpose of this review is to discuss the role of hypoxia and angiogenesis in the pathogenesis of rheumatoid arthritis. RECENT FINDINGS: Vascular pathologic change, in the form of angiogenesis, is important in the perpetuation of rheumatoid arthritis and, in the form of endothelial dysfunction, contributes to associated cardiovascular comorbidity. Recent data suggest that tumor necrosis factor-alpha blockade may modify the vascular pathologic changes in rheumatoid arthritis. Angiogenesis is a prominent feature of rheumatoid synovitis. Emerging evidence based on ultrasonographic vascular imaging and angiogenic biomarkers implicates angiogenesis in the active phase of erosive disease. Many factors contribute to the profoundly hypoxic environment that can arise within the joint affected by rheumatoid arthritis. At a cellular level, hypoxia is detected by a mechanism that regulates cytoplasmic concentrations of hypoxia-inducible factor-1alpha. After translocation to the nucleus, hypoxia-inducible factor-1alpha binds its partner hypoxia-inducible factor-1beta to form a heterodimeric, functional transcription factor, hypoxia-inducible factor-1, which activates a gene program associated with angiogenesis, glycolysis, and adaptation to pH. SUMMARY: Despite the luxuriant vasculature associated with rheumatoid arthritis synovitis, the joint affected by rheumatoid arthritis is hypoxic. Repetitive cycles of hypoxia and reoxygenation together with oxidants produced by phagocytic cells promote chronic oxidative stress within the microenvironment of the affected joint, leading to the generation of reactive oxygen species with the potential to contribute to tissue damage.